Transação tributária federal à luz da Lei 13.988/2020 e sua regra matriz - Pereira, Tamires Pacheco Fernandes (2022)
This work has the objective of tax transaction in its federal scope in reason for the enactment of Law n. 13.988/2020, born from the conversion of the Provisional Measure of the legal taxpayer, MPV nº 899/2019 of the Federal Government that currently has credit in stock in the Active Federal Debt of R$ 2.719.624.387.573,04. In the first part of the work, we broach the transaction in Brazil, concepts and in the field of civil law in the law of legal nature, impact of the Civil Procedure Code of 2015, we recall the principles focusing on the principle of unavailability of public law, so acclaimed by the doctrine. In the second part, we broach the information requirements in the CTN, existence of law, mutual concessions, purpose of termination of litigation and existence of litigation. In the third part, we analyze Law n. 13.988/2020, the transaction modalities, the matrix rule, types of credit that can be transacted, general conditions, benefits, impediments and causes of termination of the transaction. In the last part, we draw attention to the effects of the transaction, much criticized by the doctrine, if in fact it is a cause of suspension or extinction of the tax credit. In conclusion, it is a promising institute in the resolution of controversies between the State and taxpayers at the federal level, provided that it meets the legal requirements